Surviving in chronic conflict environments the experience of IDPs in Central Mindanao - Quitoriano, Eddie Ll (Save the Children UK, 2004)
This CD-ROM contains the report written by Eddie L. Quitoriano with Theofeliz Marie P. Francisco, a PPT presentation of the report. Also included are images and drawings.